Public Accountability Analysis And Government Performance Measurement - Hermansyah , Eko (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This article was created to provide an overview of how important the role of public accountability and public transparency is in governance. Accountability can be seen from an accounting perspective, a functional perspective and an accountability system perspective. Several techniques were developed to strengthen accountability systems through methods widely used in accounting, management and research such as management by objectives, performance budgeting and operations research. Performance measurements are grouped into three categories of indicators, namely (1) indicators to measure service effort, (2) indicators to measure service achievement, and (3) indicators linking effort to achievement. The Accountability System is also an obligation to provide accountability or answer and explain the performance and actions of a person/legal entity/leader of an organization to parties who have the right or obligation to hold accountable.